Crystal structure of oxide layers on Mo‐added Fe‐Cr Alloys studied by GIXS and XPS1. (28th March 2014) - Nagoshi, M.; Makiishi, N.; Hamada, E.; Kawano, T.; Ishii, K.; Okada, S.; Sato, M.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The grazing incident X‐ray scattering (GIXS) and XPS measurements were carried out for as‐polished surfaces of polycrystalline Fe‐Cr ferritic alloys with and without Mo. The GIXS patterns from the oxide layers consist of the diffraction peaks from Cr2O3 and the broad scattering peaks. The intensities of the diffraction peaks tended to increase as the thickness of the oxide layers on the samples became larger and their content of Cr estimated by XPS decreased. However, the intensities of the diffraction peaks changed independently of the alloy compositions as well as the dependence of the thickness and Cr content of the layers on the alloy compositions. Contaminations such as Na and S spontaneously mixed during polishing treatments are considered to be a possible reason of the formation of crystalline Cr2O3 on the surfaces. Copyright © 2014 John Wiley & Sons, Ltd.